Effectiveness of homeopathic treatment in complicated or laborious extractions - Ana Caridad López Vantour; Karelia Quevedo Peillon; Maricel Marquez Filiu; María Elena García Colome; Ana Maria Quinzán Luna (Centro Provincial de Información de Ciencias Médicas, 2017)
A therapeutic intervention study was carried out in 70 patients from 19 to 75 years, belonging to "Camilo Torres Restrepo" University Polyclinic in Santiago de Cuba, from June, 2014 to February, 2015, with the aim of evaluating the effectiveness of homeopathic treatment with Hyperycum and Arnica montana in complicated or difficult tooth extractions in these patients. For this purpose, two groups were made in an alternate way: a study group which received homeopathic treatment, and a control group, to which the conventional therapy was applied. Clinical exam and interrogation were carried out to those who were affected and the variables were collected in a chart for data. To evaluate the results Chi square non parametric test was applied. It was concluded that the homeopathic treatment was more effective than the conventional one, since it decreased the symptoms and signs in the shorest possible time.